The Working Group on Urban Sparrows - 5th International Meeting: České Budějovice 2016 (3-4 november) - Havlíček, Jan; Laet, Jenny De (Zielona Góra: University of Zielona Góra, Faculty of Biological Sciences)
The Working Group on Urban Sparrows (WGUS) was set up in 2006, after the symposium ?the status of the House Sparrow Passer domesticus in the urban environment? on the 24th International Ornithological Congress. WGUS associate researchers investigate population changes and their potential causes in sparrows Passer, especially in urban and suburban habitats. To foster exchange of ideas and current results among WGUS member, the meetings in London, Newcastle and Ghent were arranged. The 5th meeting was held in České Budějovice, Czech Republic in November. 2016. Here we publish the abstracts & outcomes from the meeting.
Keywords: wróblowe; ornitologia; konferencja